Desarticulación de la máquina antropológica en “Axolotl” de Julio Cortázar. (Altre Modernità, 2021)
ABSTRACT: Julio Cortázar's literature has expressed the animal question on many occasions, giving evidence of his ability to expose animals' perception of time, space, and visual field, the umwelt, the medium of the animal (vox Uexküll). This article analyzes the work “Axolotl” (1956), as a crucial piece of Cortázar's concerns in his search to confront the anthropological machine, seen it as the form of denial of human animality and the subordination of what is animal, according to Giorgio Agamben. Consequently, this article's hypothesis maintains that Axolotl, rather than expressing a human-animal confrontation, affects the becoming-animal as a way to access an ontological possibility. Thus, the becoming-animal (Deleuze and Guattari) forms a device of opposition and disarticulation of the anthropological machine through lines of flight and deterritorializations. Furthermore, on the discursive plane, this fiction raises the possibility for a zoo-autobiography, which implies a shared capacity to produce a self, animal and human, discourse, considering both as autobiographical animals (Derrida).
Keywords: Becoming an animal; anthropological machine; Latin American literature; Julio Cortázar; zoo-autobiography